2018
DOI: 10.1111/are.13730
|View full text |Cite
|
Sign up to set email alerts
|

Crude protein levels in diets for two growth stages of Nile tilapia (Oreochromis niloticus) in a biofloc system

Abstract: Biofloc technology (BFT) provides an additional feed source for aquatic organisms through the conversion of waste in microbial flocs. Because of this, the suitable protein level in a diet for animals in this system could be different from those in conventional systems. Our objective was to determine the suitable protein level in the diet of Nile tilapia juveniles reared with BFT. Two experiments were carried out with tilapia weighing~10 g (first experiment) and about 50 g (second experiment) during 61 and 98 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 40 publications
4
42
6
Order By: Relevance
“…Variations on biofloc composition were related to the different BFT trials. Comparing other experiments that evaluated CP in BFT, the results of the present study were higher than 37.93 and 38.41% CP (Azim & Little, ) and 15.09 to 20.31% CP (Silva et al, ). According to Crab et al (), different carbon sources and ratios influence the CP content of biofloc, which can reach 28–58%.…”
Section: Discussioncontrasting
confidence: 67%
See 4 more Smart Citations
“…Variations on biofloc composition were related to the different BFT trials. Comparing other experiments that evaluated CP in BFT, the results of the present study were higher than 37.93 and 38.41% CP (Azim & Little, ) and 15.09 to 20.31% CP (Silva et al, ). According to Crab et al (), different carbon sources and ratios influence the CP content of biofloc, which can reach 28–58%.…”
Section: Discussioncontrasting
confidence: 67%
“…The values obtained in this experiment from SS and TSS were within the recommended limits for BFT (Avnimelech, ). However, Azim and Little () and Silva et al () observed TSS reaching up to 1,000 mg/L in different studies with tilapia fed different CP concentrations.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations